PENGARUH PELATIHAN ASUHAN PERSALINAN NORMAL TERHADAP KOMPETENSI BIDAN TENTANG MANAGEMEN AKTIF KALA III PERSALINAN KABUPATEN BOYOLALI - Ardiani Sulistiani; Sri Sukitin (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
In Boyolali cause of maternal mortality due to postpartum hemorrhage was 44.4%. NormalDelivery Care training is the concept of Active Management of third stage of labor with theleadership of the third stage of labor is done proactively with the aim of producing a moreeffective uterine contractions. Objective: To determine the effect of the Normal Delivery CareTraining Midwives competency of third stage of labor Active Management. ResearchMethodology: observational research using cross sectional design. As a means of data collectionused questionnaires and checklist sheet. Analysis of the data used in this study is the use of chisquare.The sample in this study a number of 66 midwives and retrieval using purposivesampling technique.  Based on the results of research on the effect of normal delivery caretraining to midwives about the competence of the active management of the third stage inBoyolali number 66 midwives then showed that the majority of training midwives have a goodknowledge of as many as 26 were (39.4%) and skilled a total of 29 midwives (43.9%), themajority of respondents were not APN had no knowledge of either the 24 midwives (36.4%)and un skilled midwives were 21 (31.8%). Based on chi-square analysis of data with SPSS 18.0with a degree of confidence of 95% and a significant degree the results obtained 0.05 p value0.000 < 0.05, which means that there is an influence of normal delivery care training tomidwives about mangemen active competence third stage of labor. Based on our researchrevealed that there is significant relationship between the effect of normal delivery care trainingto midwives about the competence of the active management of the third stage of labor. Keywords: Normal Delivery CareTraining, CompetencyMidwife